Students’ Perceptions of Cooperative Learning Experiences in EFL Reading Classes - Nadiya Andriana; Pasca Kalisa (English Education:Journal of English Teaching and Research, 2026)
This study explores students' perceptions of cooperative learning in EFL reading classes at the secondary school level in Indonesia. It aims to examine students’ engagement and social dynamics during cooperative learning activities. A case study design was employed, involving 35 students who completed a 14-item Likert-scale questionnaire assessing motivation, self-confidence, anxiety reduction, and peer support. In addition, semi-structured interviews were conducted with eight students to gain deeper insights into their experiences. The results indicate that most students perceive cooperative learning positively. The quantitative data show that cooperative learning helps reduce students’ anxiety and enhances peer support. The qualitative findings reveal that cooperative interaction facilitates students’ understanding of complex reading texts; however, challenges such as unequal participation among group members were also identified. The effectiveness of cooperative learning appears to depend not only on group formation but also on strategies that ensure equitable participation, highlighting the importance of the teacher’s active role in managing student interactions and the structuring of participation as a key component in cooperative learning models.